Assessing Critical Thinking in Mathematics Education: A Systematic Review and Analysis Using the PRISMA Framework - Azmi, Irham; Abdullah, Mohd Faizal Nizam Lee; Alwadood, Zuraida; Calaminos, Franklin P. (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Developing critical thinking skills is paramount in the realm of mathematics education in today's era. It's crucial to monitor learners' advancements in critical thinking, as such insights are valuable for enhancing educational methodologies. Recognizing this, the availability of tools for evaluating critical thinking abilities is vital for fostering students' proficiency in these skills. This research sets out to review existing literature on the assessment of critical thinking capabilities within the sphere of mathematics. A thorough analysis was conducted on relevant scholarly articles focusing on the evaluation of critical thinking in mathematics education. The study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, which includes the steps of identification, screening, eligibility, and inclusion. Literature from the SCOPUS database was meticulously reviewed, given its esteemed status in providing precise data for international research indexing. Data from the selected documents were visualized using VOSviewer software. Adhering to the PRISMA methodology, findings reveal the significance of critical thinking in the field of mathematics education and highlight various methods and tools that can assess these skills within mathematical contexts. Nonetheless, there remains a gap in consensus on the definition of critical thinking due to the diverse array of theories and perspectives, leading to variability in assessment standards, particularly in mathematics education. Thus, there is a pressing need to precisely define critical thinking within the mathematical domain and to develop accurate tools for its assessment.